O Exame Nacional de Certificação se Competências de Jovens e Adultos - Encceja sob o olhar dos estudantes: ensejos e /ou impertinências? - Valadares, Talita (2023)
This research investigates the migration of high school students from Basic Education to certification by the Brazilian National Exam for the Certification of Competencies of Young People and Adults (Encceja), between 2017 and 2019 in the municipality of Ouro Preto (MG) from the students' perspective. The aim of this study was to critically analyze the extent to which the induction of the exam enabled the personal and professional advancement of young people and adults who migrated from secondary school to basic education certification in the context of the federal and state networks in the municipality. The hypothesis that guided the research is that young people choose to migrate for various reasons, supposedly to meet personal demands, sometimes to enter the job market, to continue their studies at higher education level. The theoretical and epistemological contribution involved interlocutions at the interfaces of the Educational Policy, Sociology, Critical Theory and Political Sociology of Education, Educational Evaluation and the field of Youth and Adult Education, with Paulo Freire as the connecting and producing link. With a qualitative approach, the study's methodological option is the policy cycle based on Ball and Mainardes and documentary analysis based on Cellard. The instruments used to produce the data were the questionnaire and the life narrative interview from the perspective of Bertaux's ethnosociology. The results show, based on the subjects' narratives, in the context of practice, that young people interpret the policy in an individualized way based on their experiences, unaware of the purpose for which the Exam was created. There is a positive evaluation of Encceja, with failure being the main reason young people migrated from basic education to EJA certification, as well as speeding up their studies and allowing access to the job market and university. On the other hand, the migration process confirms. The thesis is that the Encceja has been restricted to flow correction and has also led young people in the regular schooling process, therefore not from the EJA, to migrate to certification to the detriment of completing their schooling in Basic Education, giving up the training process to which they are entitled. Encceja is an example of the overlapping of public education policies at national level, contributing to the flexibilization of secondary education and the hollowing out of basic education and youth and adult education.